Altered food preferences and chemosensory perception during chemotherapy in breast cancer patients: A longitudinal comparison with healthy controls. (January 2018) - de Vries, Y.C.; Winkels, R.M.; van den Berg, M.M.G.A.; de Graaf, C.; Kelfkens, C.S.; de Kruif, J.Th.C.M; Göker, E.; Grosfeld, S.; Sommeijer, D.W.; van Laarhoven, H.W.M.; Kampman, E.; Boesveldt, S.
Highlights: Altered food preferences during chemotherapy are macronutrient specific. Chemotherapy mainly affects taste perception. Reported taste perception is related to liking of food. Abstract: Changes in food preferences and chemosensory function are frequently reported during chemotherapy, but the nature of these changes are largely unknown. We followed and characterized food preferences, taste and smell function over chemotherapy treatment in breast cancer patients and compared to women without cancer. Furthermore, we assessed associations between taste and smell function and food preferences in breast cancer patients. Women with newly diagnosed breast cancer (n = 28) completed test sessions before, halfway, shortly after, and six months after chemotherapy. Twenty-eight women without cancer were tested at similar time points as control. During test sessions, food preferences were assessed with the Macronutrient and Taste Preference Ranking Task. Self-reported taste and smell function were tested on a visual analogue scale. Objective taste and smell function were assessed with Taste Strips and Sniffin' Sticks. Breast cancer patients liked high-protein, high-fat, sweet, and savoury products less during chemotherapy, which returned to baseline six months after chemotherapy, while the control group was stable over time. Chemotherapy led to a decreased taste and smell function which recovered six months after chemotherapy. A better self-reported taste was associated with higher liking of high-protein, low-energy, savoury and sweet products. Breast cancer patients undergoing chemotherapy have altered food preferences for certain macronutrients, but not specifically for sweet or savoury tastes. Chemotherapy has a transient influence on food preferences and chemosensory function, of which patients should be informed prior to treatment, and which should be monitored during treatment due to the consequences for nutritional intake and quality of life.